Towards the Family's Salvation : examining the displacement of the (F)ather in selected religious family dramas of Ibsen and Strindberg resulting in the creation of a new text - Gerber, Andre Kruger (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA)--Stellenbosch University, 2014.